Epistemic injustice and the psychiatrist. Issue 1 (5th January 2023) - Kious, Brent M.; Lewis, Benjamin R.; Kim, Scott Y. H.
Abstract: Background: Psychiatrists depend on their patients for clinical information and are obligated to regard them as trustworthy, except in special circumstances. Nevertheless, some critics of psychiatry have argued that psychiatrists frequently perpetrate epistemic injustice against patients. Epistemic injustice is a moral wrong that involves unfairly discriminating against a person with respect to their ability to know things because of personal characteristics like gender or psychiatric diagnosis. Methods: We review the concept of epistemic injustice and several claims that psychiatric practice is epistemically unjust. Results: While acknowledging the risk of epistemic injustice in psychiatry and other medical fields, we argue that most concerns that psychiatric practice is epistemically unjust are unfounded. Conclusions: The concept of epistemic injustice does not add significantly to existing standards of good clinical practice, and that it could produce changes in practice that would be deleterious. Psychiatrists should resist calls for changes to clinical practice based on this type of criticism.